PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN FIXED ASSET RATIO TERHADAP STRUKTUR MODAL PADA PERUSAHAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Primadayani, Syurti; Nurhayati, Nurhayati (Komunitas Manajemen Kompetitif, 2026)
study aims to determine how much influence the size of the company, liquidity and fixed asset ratio together and partial to the capital structure with 30 samples in the consumer goods industry companies in Indonesia Stock Exchange. The analytical method used is panel data regression analysis. The result of partial research is that firm size is not influential and not significant, liquidity has negative and significant effect, while fixed asset ratio has positive and significant effect to capital structure. Simultaneously significant effect on capital structure. Finally, the authors suggest to the next researcher in order to add variables and research samples. And for the company is advised to put more of its own capital than foreign capital, because the higher the foreign capital obtained by the company, the company's debt repayment rate is higher.